Pengaruh Kuat Arus Las Terhadap Sifat Mekanis dan Struktur Mikro Sambungan Las Besi Tuang Kelabu menggunakan Elektroda Nikel dengan Proses Pengelasan SMAW - Topan Prihantoro; Ady Setiawan; Daryono (Accurate: Journal of Mechanical Engineering and Science, 2021)
This study aims to determine the effect of welding current on the mechanical properties and microstructure of gray cast iron welding joints using nickel electrodes with the SMAW welding process. The research method used was experimental study, starting with preparing the workpiece, welding process, making test specimens and testing the weld specimens. The material to be joined is gray cast iron metal with a butt joint of a 60 ° open seam V open angle. The welding process used uses SMAW with a current of 80 Amperes, 85 Amperes and 90 Amperes. The added material used was an ENiFe-Cl type CIN 2 electrode with a diameter of 2.6 mm. Hardness testing was carried out using the Vickers method and microstructure testing using an optical microscope. The results showed that the maximum hardness value of the parent metal occurred at the welding current strength of 85 Amperes, which was 192.17 VHN, then the maximum hardness value of the HAZ area occurred at the welding current strength of 85 Amperes, which was 203.46 VHN, while the maximumhardness value of the weld metal was 203.46 VHN. metal) occurred at a welding current of 90 Amperes, which was 211.18 VHN. The results of the microstructure observation showed that the matrix formed on the parent metal was pearlite withgraphite in the form of flakes. The micro structure formed in the HAZ area was a martensite structure. Meanwhile, the microstructure of weld metal consists of an austenite matrix with an even distribution of graphite particles.